PENGARUH KUALITAS SISTEM, INFORMASI, LAYANAN, DAN PERCEIVED COERCION TERHADAP KEPUASAN WAJIB PAJAK PENGGUNA CORETAX - Muhammad Prans Panca Renta; Nurul Syahbela; Amirul Bahar (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2026)
This study aims to analyze the influence of system quality, information quality, service quality, and perceived coercion on taxpayer satisfaction among CoreTax users and to expand the application of the Information System Success Model to the context of mandatory system use. The research method used was a quantitative approach, collecting primary data through questionnaires from 119 taxpayers using CoreTax. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 3.2, through testing of measurement and structural models. The results indicate that system quality and information quality have a positive and significant effect on taxpayer satisfaction among CoreTax users, while service quality and perceived coercion do not significantly influence taxpayer satisfaction. Information quality is the most dominant variable influencing taxpayer satisfaction, demonstrating the importance of accuracy, completeness, relevance, and ease of understanding of information in supporting the fulfillment of tax obligations. The conclusion of this study indicates that the success of CoreTax implementation is determined more by the system's ability to provide quality tax information and effective system performance than by supporting service factors or perceived coercion in using the system. Keywords: Coretax; Taxpayer Satisfaction, Information Quality, Service Quality, System Quality